Insights into nutrition, flavor and edible quality changes of golden pomfret (Trachinotus ovatus) fillets prepared by different cooking methods - Xiong, Tian; Mei, Xin; Wu, Yanyan; Wang, Lan; Shi, Jianbin; Sui, Yong; Cai, Sha; Cai, Fang; Chen, Xueling; Fan, Chuanhui (Frontiers in Nutrition, 2023)
Introduction In recent years, Asia has seen an increase in demand for golden pomfret (Trachinotus ovatus). Especially in instant (ready-to-eat) and prepared (ready-to-cock) food processing industry. Thermal processing is a vital part of food processing. However, no comprehensive analysis has been reported on its flavor, nutrition and edible quality changes during the key thermal processing. Methods Accordingly, in this study, we evaluated the effects of different cooking methods (steaming, frying, microwaving and baking) on the color, texture, cooking loss, nutrition composition, volatile flavor substances and other indicators of golden pomfret filets. Results and Discussion The results showed that the steamed samples (SS) had the lowest cooking loss and fat content, the highest moisture content, complete appearance and the lowest levels of hardness and chewiness. Fried samples (FS) had a notable difference in fatty acid composition. The content of unsaturated fatty acids (UFAs) increased significantly, while the relative content of eicosapentaenoic acid (EPA) + docosahexaenoic acid (DHA) decreased from 7.88 to 1.42%, lower than other groups. The essential amino acid index (EAAI) of microwaved samples (MS) was 94.89, which was higher than other groups. Baked samples (BS) had the highest relative content of umami amino acids (UAAs) and sweet amino acids (SAAs), which was 8.08 mg/100 mg and 5.19 mg/100 mg, respectively. Hexanal and nonanal were detected in control samples (CK), SS, FS, MS and BS. While pyrazine compounds were detected only in FS and BS. Steaming and microwaving treatment of golden pomfret resulted in better nutritional preservation, which was more conducive to human health. Frying and baking treatment of golden pomfret had better taste and flavor and higher sensory scores. The nutrition, flavor and edible quality of golden pomfret under different cooking methods were related and interactive. Cooking loss and fat content can be used as simple evaluation indicators to compare the overall quality of different cooking methods. This study provides a reference for the thermal processing technology and industrial production of golden pomfret.